The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1042/bj3440145
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding activity of the transcription factor upstream stimulatory factor 1 (USF-1) is regulated by cyclin-dependent phosphorylation

Abstract: The ubiquitous transcription factor upstream stimulatory factor (USF) 1 is a member of the bzHLH (leucine zipper-basic-helix-loop-helix) family, which is structurally related to the Myc family of proteins. It plays a role in the regulation of many genes, including the cyclin B1 gene, which is active during the G2/M and M phases of the cell cycle and may also play a role in the regulation of cellular proliferation. We show that the affinity of recombinant USF-1 for DNA is greatly increased by treatment with act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…As described in the present study, it is highly possible that USF1/USF2 also functions as a Ca 2ϩ signal-stimulated transcription factor in neurons. It has been reported that the phosphorylation of USF1 enhanced its DNA binding activity (36); quite recently, Galibert et al (37) reported that phosphorylation of USF1 at Thr-153 increased its transcriptional activity. In addition, the activation of gene transcription by USF1/USF2 could be mediated by CBP/p300 (38).…”
Section: Discussionmentioning
confidence: 99%
“…As described in the present study, it is highly possible that USF1/USF2 also functions as a Ca 2ϩ signal-stimulated transcription factor in neurons. It has been reported that the phosphorylation of USF1 enhanced its DNA binding activity (36); quite recently, Galibert et al (37) reported that phosphorylation of USF1 at Thr-153 increased its transcriptional activity. In addition, the activation of gene transcription by USF1/USF2 could be mediated by CBP/p300 (38).…”
Section: Discussionmentioning
confidence: 99%
“…E boxes consist of the core hexanucleotide sequence CANNTG and can bind proteins from the basic helix-loop-helix (bHLH) family that includes the aryl hydrocarbon receptor, upstream stimulatory factor, and sterol regulatory elementbinding protein (32). Protein phosphorylation has been shown to either enhance (30,33) or disrupt the DNA binding (34) of some bHLH factors and/or to modify their transcriptional activity (35,36). In fact the bHLH factors heart and neural crest derivatives expressed 1 and 2 interact with the protein phosphatase 2A targeting subunit B56␦ (37).…”
Section: Discussionmentioning
confidence: 99%
“…and P.J.H., unpublished). Phosphorylation of USF-1 is necessary for DNA binding (Cheung et al, 1999) and, consistent with this requirement, the predominant form of USF-1 eluted from PAI-1 deoxyoligonucleotide affinity columns co-migrated with the 45 kDa (phospho-USF-1) species (Fig. 5).…”
Section: Usf-1 Is a Pai-1 E-box Binding Proteinmentioning
confidence: 74%
“…The upper-lower doublet retardation pattern was evident as early as 2 hours after scrape injury (2 hr edge) and, like growing RK cultures (G), addition of USF-1 antibodies specifically supershifted this upper complex. phosphorylation requirement of certain HLH factors for E-box motif recognition (Nozaki et al, 1997;Cheung et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation